NALYSIS OF THE ROLE OF ENTREPRENEURIAL SELF-EFFICACY AS MEDIATION AND BUSINESS COLLABORATION AS MODERATION IN THE RELATIONSHIP BETWEEN ENTREPRENEURSHIP EDUCATION AND BUSINESS PERFORMANCE - Deylan Jevon Gunawan; Damelina Basauli Tambunan (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
The entrepreneurship rate in Indonesia stands at 3.35% of the total workforce, highlighting the need for strategic efforts to foster more entrepreneurs. Higher education institutions also bear responsibility for this initiative. To address this, the present study focuses on analyzing business performance at a specific university, aiming to examine the relationship between entrepreneurship education and business performance through the mediating role of entrepreneurial self-efficacy and the moderating effect of business collaboration. The study involved 94 respondents selected via purposive sampling, with criteria including students from a private university in Surabaya, Class of 2022, who were registered in a family business guild. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal the following Entrepreneurship education has a significant positive effect on entrepreneurial self-efficacy (H1). Entrepreneurial self-efficacy significantly influences business performance (H2). Entrepreneurship education also directly impacts business performance (H3). Entrepreneurial self-efficacy partially mediates the relationship between entrepreneurship education and business performance (H4). Business collaboration does not moderate the relationship between entrepreneurship education and business performance (H5).